1470. Epidemiology of Invasive Pneumococcal Disease (IPD) Following 18 years of Pneumococcal Conjugate Vaccine (PCV) Use in the United States. (31st December 2020) - Pilishvili, Tamara; Gierke, Ryan; Farley, Monica M; Schaffner, William; Thomas, Ann; Reingold, Art; Harrison, Lee; Holtzman, Corinne; Burzlaff, Kari; Petit, Susan; Herlihy, Rachel; Torres, Salina; et al.
Abstract: Background: PCVs have been recommended for U.S. children since 2000. A 7-valent vaccine (PCV7) was introduced in 2000. This was replaced by a 13-valent vaccine (PCV13) in 2010. PCV13 was also recommended for adults aged ≥ 65 years in August 2014. We evaluated PCV impact on IPD. Methods: IPD cases (isolation of pneumococcus from sterile sites) were identified through CDC's Active Bacterial Core surveillance during 1998-2018. Isolates were serotyped by Quellung or whole genome sequencing and classified as PCV13-type and non-vaccine-type (NVT). Incidence rates (cases/100, 000) were calculated using U.S. Census Bureau population denominators. Results: From 1998 through 2018, overall IPD rates among children aged < 5 years decreased by 93% (from 95 to 7 cases/100, 000). PCV13-type IPD decreased by 98% (from 88 to 2 cases/100, 000). Among adults aged ≥ 65 years, overall IPD rates decreased by 60% (from 61 to 25 cases/100, 000). PCV13-type IPD rates declined 86% (from 46 to 7 cases/100, 000). Declines were most dramatic in the years following PCV7 introduction, with additional declines after PCV13 introduction in children (Figures 1 and 2). Serotypes 3, 19A, and 19F caused most of the remaining PCV13-type IPD. NVT IPD rates did not change significantly among children. Among adults aged 50-64 years, NVT IPD increased by 83% (from 6 to 12 cases/100, 000) (p< 0.01). Among adults aged ≥ 65 years, NVT IPD increased by 22% (from 15 to 18 cases/100, 000) (p< 0.01). The most common NVTs in 2018 were 22F (10% of all IPD), 9N (7%) and 15A (5%). Among children, the proportion of cases with meningitis increased from 5% to 14% (p< 0.01), and the proportion with pneumonia/empyema increased from 17% to 31% (p< 0.01). Among adults, the proportion of cases with meningitis did not change (3%), while the proportion with pneumonia/empyema increased from 72% to 76% (p=0.01). Figure 1: Incidence of invasive pneumococcal disease among children aged < 5 years, 1998-2018 Figure 2: Incidence of invasive pneumococcal disease among adults aged ≥ 65 years, 1998-2018 Conclusion: Overall IPD incidence among children and adults decreased following PCV introduction for children, driven primarily by reductions in PCV-type IPD. NVT IPD increased in older adults, but these increases did not eliminate reductions from PCV13-type IPD. Disclosures: Lee Harrison, MD, GSK (Consultant)Merck (Consultant)Pfizer (Consultant)Sanofi Pasteur (Consultant)